1988
DOI: 10.1111/j.1471-4159.1988.tb03032.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Micromethod for the Quantitative Assessment of Central Demyelination

Abstract: We report the development of a simple and reliable method for the study of demyelination in vitro based on the measurement of 2':3'-cyclic nucleotide 3'-phosphodiesterase in isolated myelin. Using only small quantities of myelin (equivalent to 100 micrograms of myelin protein) the system was tested under conditions that are believed to approximate those found at the site of an inflammatory demyelinating lesion. Treatment with a combination of trypsin, phospholipase A2, and lysophosphatidylcholine was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Specific T cells can release lymphokines which lead to the recruitment, accumulation, and activation of additional brain macrophages in the CNS tissue. Brain macrophages can also produce tumor necrosis factor alpha, which induces oligodendrocyte necrosis and demyelination (6,17,36), prostaglandin E (16), and other mediators such as leukotrienes and phospholipases, proteinases that have been shown to have high myelinolytic activity (7,42). The amount of tumor necrosis factor alpha (37) and of IL-1 (40) in the cerebrospinal fluid and sera of patients with MS has been correlated with the intensity of the disease.…”
Section: Notesmentioning
confidence: 99%
“…Specific T cells can release lymphokines which lead to the recruitment, accumulation, and activation of additional brain macrophages in the CNS tissue. Brain macrophages can also produce tumor necrosis factor alpha, which induces oligodendrocyte necrosis and demyelination (6,17,36), prostaglandin E (16), and other mediators such as leukotrienes and phospholipases, proteinases that have been shown to have high myelinolytic activity (7,42). The amount of tumor necrosis factor alpha (37) and of IL-1 (40) in the cerebrospinal fluid and sera of patients with MS has been correlated with the intensity of the disease.…”
Section: Notesmentioning
confidence: 99%
“…However, there is some evidence that a relapse may be initiated peripherally, for recent studies on lymphocyte migration have found CD2-positive cells crossing the blood-brain barrier from the blood into the CSF in progressive MS (Hafler & Weiner, 1987). It has also been suggested that cells may circulate from the CNS to the blood (Oehmichen et al, 1979;Wekerle et al, 1986). Therefore, the Correspondence: Samantha J. Owen, Department of Neurochemistry, Institute of Neurology, London WCIN 3BG, UK.…”
Section: Introductionmentioning
confidence: 99%